Foreword - GURGU, Elena (Annals of Spiru Haret University. Economic Series, 2018)
Shanta Devarajan, who is the Senior Director at the Development Economics – World Bank, said recently, in a forecasting about global economic growth at the beginning of 2018, that currently there is a set of optimistic projections for economic growth around the world. Ten years after the global financial crisis, every economic region – from the U.S. to Europe to Asia, Africa, and Latin America – is seeing an uptick in growth. One reason for the optimism is that economic growth was surprisingly better than anticipated in 2017. Almost every growth forecast at the beginning of the year was revised upward by the end of the year. Global growth, projected by the World Bank to be 2.7 % in January 2017, was estimated at 3 percent in December, with expectation to be at 3.1 percent in 2018. Furthermore, stock markets are booming. And the factors that caused growth to be subdued in the past – a slowdown in investment and trade and low commodity prices – are rebounding. Consequently, developing country growth is forecasted at a robust 4.5 percent in 2018, accelerating to 4.7 percent in the subsequent two years. This growth is not just driven by China, although the country’s economy is projected to grow at a robust 6.4 percent in 2018. Low-income countries’ growth will rise to 5.4 percent in 2018, accelerating to 5.6 percent in 2019-2020, as metal and mineral prices strengthen.